Numerical Simulation Research on the Pressure Relief and Permeability Enhancement Mechanism of Large-Diameter Borehole in Coal Seam. (26th April 2022) - Nian, Jun; Zhao, Bo; Zhang, Wei
Abstract : In order to achieve high-efficiency extraction of coal seams with large-diameter borehole and large flow rates, and to rapidly reduce coal seam gas content and pressure, a large-diameter borehole coal seam pressure relief and permeability enhancement technology is proposed. In this paper, numerical simulation is used to study the mechanism of pressure relief and permeability enhancement in coal seams with large-diameter boreholes, and the evolution of stress, cracks, gas, and permeability of coal bodies around boreholes with different diameters is discussed. The research results show that the stress changes in the coal body around the borehole are symmetrically distributed around the borehole. The stress evolution controls the evolution of the coal body's cracks. Firstly, damage occurs around the borehole and then extends to the upper left and right corners, like a butterfly spreading its wings. The crushing zone increases with the increase of the hole diameter, and the impact radius of the 100-mm, 200-mm, 300-mm, and 350-mm diameter borehole rupture is 0.375 m, 0.65 m, 1.0 m, and 1.25 m, respectively. The rupture radius of the double 350-mm diameter borehole can reach 2.4 m. The larger the diameter of the borehole, the more fissures will be produced, and the air permeability of the coal body in the affected coal seam area will obviously increase. The research results provide theoretical support for gas drainage in soft, low-permeability, high-gas coal seams.